Penguatan Gotong Royong Pangan melalui Pemberdayaan Dapur Masjid: Program Dapur Mustikarasa Ramadhan di Aceh - Agustinar Tina; Nurjanah; Rafiza Zuliani; Zulfa Eliza; Nova Rianti; Mira Humaira; Nurazizah; Dessy Asnita (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2026)
Food access vulnerability among certain community groups requires stronger social awareness and community participation in food provision. This community service program aimed to describe the implementation and outcomes of the Dapur Mustikarasa Ramadhan 2026 Program in strengthening food solidarity through the empowerment of mosque kitchens and volunteer participation in Aceh. The program employed a participatory approach involving 14 mosque kitchens across four areas: Aceh Tamiang, North Aceh, Banda Aceh, and Langsa. Activities included preparation, organization, food processing, hygiene and sanitation practices, packaging, distribution, documentation, and evaluation, organized through the 5M principle: collecting, preparing, processing, serving, and distributing. The results showed that the mosque kitchen network functioned as a basis for organizing food activities, while volunteers and community members participated in food preparation, processing, packaging, and distribution. The program targeted the provision of 3,400 iftar meal packages through 14 mosque kitchens. These outcomes indicate that mosque kitchens and volunteer networks can be mobilized as community assets for organizing collective food initiatives during Ramadhan. The program highlights the importance of integrating local facilities, community participation, and social care in developing community-based food initiatives. Keywords: Mosque Kitchen; Food Solidarity; Community Participation; Volunteers; Ramadhan